2010
DOI: 10.1002/ijc.25644
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of a multianalyte serum biomarker panel to identify lymph node metastases in non‐small cell lung cancer with circulating autoantibody biomarkers

Abstract: We recently reported the development of a multianalyte serum algorithm to identify nodal status in non-small cell lung cancer (NSCLC) patients facing an anatomic resection with curative intent. This study aims to enhance the overall performance characteristics of this test by adding autoantibody biomarkers identified through immunoproteomic discovery. More specifically, we used sera from 20 NSCLC patients to probe 2-D immunoblots of HCC827 lysates for tumor-associated autoantigens. Relevant differences in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…2,19 Autoantibody signatures might be useful in cancers in which there are high-risk populations and where existing detection methods lack sensitivity and specificity, particularly in LC. 2 To identify specific LC biomarker, an immunoproteomic approach combined with MS was used to identify interesting proteins and found that three Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…2,19 Autoantibody signatures might be useful in cancers in which there are high-risk populations and where existing detection methods lack sensitivity and specificity, particularly in LC. 2 To identify specific LC biomarker, an immunoproteomic approach combined with MS was used to identify interesting proteins and found that three Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, the presence of locoregional lymph node metastases remains the most important prognostic factor and significantly guides treatment regimens. Borgia et al established a multi-analyte serum biomarker panel and identified 15 candidate biomarkers in discerning a patient's preoperative nodal status (Borgia et al, 2009;Patel et al, 2011). Some oncogene and tumor suppressor gene products in serum, such as p53, anti-p53 antibodies, sEGFR or Ras have also been utilized as NSCLC biomarkers (Brandt-Rauf et al, 1992;Angelopoulou et al, 1994;Luo et al, 1994;Baron et al, 2009).…”
Section: Serum Proteinmentioning
confidence: 94%
“…However, with recent advances in autoantibody identification, Chapman et al were able to test autoantibodies directed against various markers to develop a biomarker panel yielding up to 76% sensitivity and 92% specificity (Chapman et al, 2008). Patel et al went even further to develop an autoantibody "direct-capture" immunobead assay using selected antigens for successful detection of nonsmall-cell lung carcinoma with a sensitivity and specificity of 94% and 97%, respectively (Patel et al, 2011). Similar advances using panels of autoantibodies have been made for the diagnosis of colon cancer (Belousov et al, 2008;Chen et al, 2007;Cioffi et al, 2004;Yoshizawa et al, 2007), stomach cancer (di Mario & Cavallaro, 2008), and hepatocellular carcinoma (Li, Chen, Yu, Li, & Wang, 2008;Marrero et al, 2003).…”
Section: Autoantibodies In Cancer: Byproduct or Biomarker?mentioning
confidence: 97%